Dyadic Coping and Its Underlying Neuroendocrine Mechanisms – Implications for Stress Regulation - Zietlow, Anna-Lena; Eckstein, Monika; Hernández, Cristóbal; Nonnenmacher, Nora; Reck, Corinna; Schaer, Marcel; Bodenmann, Guy; Heinrichs, Markus; Ditzen, Beate (Frontiers in Psychology, 2019)
Previous research suggests that neuroendocrine mechanisms underlie inter-individual stress coping in couples. The neuropeptide oxytocin (OT), while regulating stress-sensitive HPA-axis activity might be crucial in this process. The purpose of this study was to examine the impact of dyadic coping abilities and OT on HPA-axis outcomes and constructive behavior during couple conflict. We conducted a secondary analysis of our previous database (Ditzen et al., 2009), assessing the modulating role of dyadic coping and intranasal OT on couple conflict behavior. The data revealed a significant interaction effect of the total score of dyadic coping and OT on cortisol responses during couple conflict, suggesting that particularly individuals with low a priori dyadic coping benefit from OT in terms of dampened HPA-activity. The results are in line with previous research suggesting OT’s central role for stress regulation and prosocial behavior. Furthermore, an interaction with dyadic coping indicates adaptations in the sensitivity of the OT system during the individual attachment and relationship history. These data add to the evidence that the neuroendocrine attachment systems influence couple behavior. Future studies of neurobiological mechanisms underlying dyadic coping will be of high relevance for the development of prevention and intervention programs.